CARACTERISATION BIOCHIMIQUE ET FONCTIONNELLE DES GRAINES DE SEPT CULTIVARS DE VOANDZOU [VIGNA SUBTERRANEA (L.) VERDC. FABACEAE] CULTIVES EN CÔTE D’IVOIRE - Séraphin, Diallo Koffi; Youssouf, Koné Kisselmina; Doudjo, Soro; Emmanuel, Assidjo Nogbou; Benjamin, Yao Kouassi; Dago, Gnakri (European Scientific Journal, ESJ, 2015)
Seeds of Bambara groundnut [Vigna subterranea (L.) Verdc.] were collected from seven cultivars in the locality of Ouangolodougou, north Côte d’Ivoire. The seeds biochemical composition was evaluated in order to determine the nutritional value of Bambara groundnut. The results showed that the moisture content varied between 7.35 to 9.02%, ash content 2.55 to 2.98 %; crude fiber 2.57 to 4.08 % and the protein content 14.61 to 20.74%. Seeds lipid composition was varying between 7.69 to 8.55 %, while the content of carbohydrate was between 54.05 to 64.50 %. Energy value was found to range from 370.02 to 388.80 Kcal per 100 g of flour. The content of phenolic compound varied from 142.43 to 205.92 mg per 100 g EG. For the functional properties, the water absorption capacity was between 199.26 to 239.75 ml per 100 g of flour, while the oil absorption capacity was between 2 to 2.12 ml / g flour. The study showed that Bambara seeds grown in that area could be a good source of nutrients. Therefore, the judicious use of Bambara seeds could be a source of additional nutrients in the diet of vulnerable population.